KARAKTERISTIK DAN VARIASI SIFAT FISIKA KAYU ACACIA MANGIUM Willd. PADA BEBERAPA JARAK TANAMAN DAN KEDUDUKAN AKSIAL-RADIAL - -, Mohamad Siarudin; Marsoem, Sri Nugroho (Balai Besar Penelitian Bioteknologi Dan Pemuliaan Tanaman Hutan, Badan Penelitian dan Pengembangan Kehutanan, Departemen Kehutanan, 2007)
This study aimed to identify characteristic and variation of A. mangium wood physical properties in different planting spacings and axial-radial position. Materials used were 8 yeats old A. mangium wood from Subanjeriji, Palembang, South Sumatera whith three spacings: 2 m x 3 m, 2 m x 4 m and 3 m x 3 m. Three sample trees in diameter of 21 cm – 25 cm from each planting spacing were taken by randomly. Speciments in each tree were taken in 3 axial position (battom, middle, and top of trunk), and 3 radial position (near pith, middle adn near bark). Parameters measured were wood density, fresh moisture content (FMC), equilibirum moisture content (EMC), total tangential shrinkage (TS), radial shrinkage (RS), longitudinal shrinkage (LS) and T/R were 0.45 gr/cm3 ; 118.40%; 7.63%; 3.53%; 0.71% and 2.23% respectively. Differences on wood physical properties of three spacing were found at FMC, TS and LS: while other propertiest were relatively not different . Based on the density, FMC an dimension change, A. magium wood grown in 2 m x 4 m plantation spacing showed the best performance, than followed by 3 m x 3 m and 2 m x 3 m. Based on axial orientation, wood density tend to increase from bottom to upper stem, FMC, EMC and TS , while other propertiest were not different. Based on radial orientation, the wood density and TS tend to increase from near the pith to near bark, while FMC and LS have reversed pattern.